2021
DOI: 10.3389/fmed.2021.713333
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review of Neurologic Complications in Adults on ECMO: Prevalence, Risks, Outcomes, and Prevention Strategies

Abstract: Extracorporeal membrane oxygenation (ECMO), a life-saving technique for patients with severe respiratory and cardiac diseases, is being increasingly utilized worldwide, particularly during the coronavirus disease 2019(COVID-19) pandemic, and there has been a sharp increase in the implementation of ECMO. However, due to the presence of various complications, the survival rate of patients undergoing ECMO remains low. Among the complications, the neurologic morbidity significantly associated with venoarterial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…ECMO can save the lives of burn patients, but it carries a high risk, and its adverse results may be caused by brain injury. [ 12 , 13 ] Indeed, nerve injury increased dramatically in ECMO patients. Studies have demonstrated that 15% to 35% of ECMO patients developed neurological damage.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…ECMO can save the lives of burn patients, but it carries a high risk, and its adverse results may be caused by brain injury. [ 12 , 13 ] Indeed, nerve injury increased dramatically in ECMO patients. Studies have demonstrated that 15% to 35% of ECMO patients developed neurological damage.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…A failure to recognize and address the presence of ABI in a timely manner can result in poor outcomes. 21,22 The presence of significant rSO 2 asymmetry can help clinicians with early detection of ABIs and intervention for ongoing ABIs.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of ICH and acute ischemic stroke range from 3.6%-16.4% and 1.7%-7%, respectively. 28 The literature suggests that most neurologic complications may arise within 6 h of ECMO initiation. 28 A study demonstrated a 31.7% mortality rate in those with ICH, they reported no significant difference in 6-month survival for patients with and without ICH, and the majority (92%) made a good neurologic recovery.…”
Section: Discussionmentioning
confidence: 99%
“…28 The literature suggests that most neurologic complications may arise within 6 h of ECMO initiation. 28 A study demonstrated a 31.7% mortality rate in those with ICH, they reported no significant difference in 6-month survival for patients with and without ICH, and the majority (92%) made a good neurologic recovery. 29 Notably, they report immediate cessation of anticoagulation upon detection of ICH, and they posit that this strategy may drastically decrease their mortality rate compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%